REMUNERASI, PELATIHAN, KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL DAN KINERJA AUDITOR DIREKTORAT JENDERAL PAJAK - Rendra K.P., Novanianto; Riduwan, Akhmad; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
Performance can be define as level of accomplishment in conducting job responsibility.Generally, performance measurement is related with three aspects, those are: quantity aspect, qualityaspect and cooperative aspect. The objective of this research is for testing and knowing the effect ofremuneration, training, emotional quotient and spiritual quotient to the auditor performance atGeneral Directorate of Taxes. This research is a quantitative study, determining sample usingpurposive sampling/judgment sampling. The data is analyzed with multiple regression analysismodels.The results of research show that remuneration, training, emotional quotient and spiritualquotient have positive effects to the auditor performance partially. The practical benefits of thisresearch can be a reference or opinion to the Directorate-General of Taxes in order to improve theability of Auditors in carrying out their tasks with more give attention related to remuneration, thedevelopment of training, upgrade of emotional and spiritual quotient (ESQ), so it can work with moreoptimal.Keywords: tax auditor, performance, remuneration, training, emotional quotient and spiritualquotient.